Effects of Hyperlipidemia on the Pharmacokinetics of Tofacitinib, a JAK 1/3 Inhibitor, in Rats - Won, Jong Mun; Choi, Hyeon Gyeom; Park, So Yeon; Kim, Jang Hee; Kim, So Hee (Pharmaceutics, 2023)
Tofacitinib, an inhibitor of Janus kinases (JAKs) 1 and 3, has been shown to be effective in the treatment of rheumatoid arthritis. The incidence of hyperlipidemia has been found to be higher in patients with rheumatoid arthritis. The present study therefore investigated the pharmacokinetics of tofacitinib after its intravenous (10 mg/kg) or oral (20 mg/kg) administration in poloxamer-407-induced hyperlipidemic (PHL) rats. The area under the plasma concentration-time curve from zero to infinity (AUC0–∞) after intravenous administration of tofacitinib was 73.5% higher in PHL than in control rats, owing to slower time-averaged nonrenal clearance (CLNR) in the former. Evaluation of in vitro metabolism showed that the intrinsic clearance (CLint) of tofacitinib was 38.6% lower in PHL than in control rats, owing to the decreased protein expression of hepatic cytochrome P450 (CYP) 3A1/2 and CYP2C11 in PHL rats. Similar results were observed in PHL rats after oral administration of tofacitinib. These results were likely due to the decreased CLNR, CLint, and P-glycoprotein (P-gp) expression in the intestines of PHL compared to control rats. Overall, these findings indicated that hyperlipidemia slowed the metabolism of tofacitinib, increasing its plasma concentrations, and that this reduced metabolism was due to alterations in expression of the proteins CYP3A1/2, CYP2C11, and P-gp in the liver and/or intestines of PHL rats.
Keywords: CYP2C11; CYP3A1/2; hyperlipidemia; P-glycoprotein; pharmacokinetics; poloxamer 407; tofacitinib